Genetic divergence and cluster analysis for bulb yield and related traits in garlic (Allium sativum) accessions at Dorze, southern Ethiopia. Issue 2 (26th April 2022) - Tesfaye, Azene
Abstract: Despite the benefits of garlic ( Allium sativum L.) in human life, only a little amount of breeding effort has been done so far. The initial stages of a systemic breeding program include the collection and evaluation of genetic variability. As a result, understanding genetic divergence and cluster dispersion between accessions is a great way to improve future crops. This study was aimed to estimate the extent of genetic divergence across 28 Ethiopian garlic accessions using 11 agromorphological traits to identify parent lines for hybridization programs. The experiment was set up with a randomized complete block design with three replicates in Dorze, southern Ethiopia, during the 2017 main harvest season. The cluster analysis revealed the existence of four divergent groups, with the greatest distance among them being between Groups I and IV ( D 2 = 4.15), and the shortest distance being between Groups I and II ( D 2 = 2.93). To obtain accessions with high grain yield and early maturing, cross from Clusters I and IV and from III and IV were obtained. Parent material should be produced among clusters rather than within clusters for future hybridization breeding efforts. Core Ideas: The genetic divergence among garlic accessions from different parts of the country is remarkable. Garlic accessions were divided into four clusters based on their 11 agronomic traits. To improve garlic production through breeding, parental material was identified. When it comes to hybridization, it is preferable to do it between clusters than within them.